Penyuluhan Mekanisme Penyelesaian Sengketa Perdata Perburuhan secara Non-Litigasi - Delfina, Dinda (Civiliza Publishing, 2025)
Labor disputes are a common issue arising from employment relationships between workers and employers, particularly concerning civil labor rights and obligations. Non-litigation dispute resolution mechanisms play an important role as an alternative to court proceedings, as they emphasize efficiency, consensus, and the preservation of harmonious industrial relations. This article aims to describe and analyze community legal counseling activities on non-litigation mechanisms for resolving civil labor disputes. The counseling focused on introducing and explaining various non-litigation methods, including bipartite negotiation, mediation, conciliation, and arbitration, as regulated under Indonesian labor law. The activity was conducted through interactive lectures and discussions to enhance participants’ understanding of their legal rights and available dispute resolution options. The results indicate an increase in participants’ legal awareness and comprehension regarding non-litigation labor dispute resolution, which is expected to reduce reliance on litigation and encourage more constructive and peaceful settlement of labor conflicts. Therefore, legal counseling on non-litigation labor dispute mechanisms is essential in strengthening access to justice and promoting sustainable industrial relations.